2006
DOI: 10.1603/0022-0493-99.5.1768
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Cry1Ab Susceptibility of European Corn Borer in Germany

Abstract: The European corn borer, Ostrinia nubilalis (Hübner), is one of the most important insect pests in corn, Zea mays L. Transgenic corn cultivars expressing Bacillus thuringiensis (Bt) toxin provide a promising crop protection strategy against European corn borer; however, management is needed to avoid resistance development of the target pest species. The aim of this work was to establish the baseline susceptibility of different European corn borer populations in Germany to be able to forecast a possible develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
46
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 18 publications
6
46
1
Order By: Relevance
“…A considerable variation in the bioactivity of the two Cry1Ab batches H3 and H4 was observed. This is in agreement with previous studies, where different Cry1Ab sources resulted in a four-to eight-fold variation in their activity (Nguyen et al, 2004;Saeglitz et al, 2006). These batch-to-batch differences could be caused by different treatments during production of these batches and/or differences in the concentration of Cry1Ab depending on the protein determination methods.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A considerable variation in the bioactivity of the two Cry1Ab batches H3 and H4 was observed. This is in agreement with previous studies, where different Cry1Ab sources resulted in a four-to eight-fold variation in their activity (Nguyen et al, 2004;Saeglitz et al, 2006). These batch-to-batch differences could be caused by different treatments during production of these batches and/or differences in the concentration of Cry1Ab depending on the protein determination methods.…”
Section: Discussionsupporting
confidence: 92%
“…the US, Spain, France, Germany and others (Chaufaux et al, 2001;Gonzáles-Núñez et al, 2000;Marçon et al, 1999;Martens et al, 1995;Saeglitz et al, 2006;Siegfried et al, 1995). Field studies on two ECB populations in Spain did not reveal any difference in their Cry1Ab susceptibilities (Gonzáles-Núñez et al, 2000), whereas small variations in susceptibility to Cry1Ab protein among different geographical ECB populations were observed in the USA and in Germany (Marçon et al, 1999;Saeglitz et al, 2006). These variations, however, could be caused by (i) an existing natural variability among geographical populations; (ii) by different activities of Cry1Ab proteins used in the different tests; or (iii) by an intrinsic variability of different bioassays when using the same insect colony and the same Cry1Ab protein batch (Farinós et al, 2004;Marçon et al, 2000; and Langenbruch, 2007;Nguyen et al, 2004;Saeglitz et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). A study with three European corn borer populations from Germany indicated that two toxin batches caused a ninefold difference in LC 50 values, although the Cry1Ab concentrations of the different batches were not compared before bioassays (18). These results suggest that Cry1Ab sources may cause pseudovariation in susceptibility whenever a new Cry1Ab batch is introduced.…”
Section: Discussionmentioning
confidence: 99%
“…Although susceptibility to Cry1Ab has been monitored since 1995, differences between batches of fermentation products or between formulated Bt insecticides and purified toxins have led to inconsistency in the measured bioactivity (B. D. Siegfried, unpublished). This inconsistency complicates the assessment of changes in insect susceptibility as estimated by 50% lethal concentration (LC 50 ) values generated by probit mortality curves or diagnostic concentrations (18). Differences in the bioactivity of Cry1Ab have been attributed to impurity of batches and to the lack of standardized protocols for Cry1Ab production and quantification.…”
mentioning
confidence: 99%